Nrf2 represses the onset of type 1 diabetes in non-obese diabetic mice. Issue 3 (March 2019) - Yagishita, Yoko; Uruno, Akira; Chartoumpekis, Dionysios V; Kensler, Thomas W; Yamamoto, Masayuki
Abstract : The transcription factor Nrf2 (NF-E2-related factor 2) plays a critical role in oxidative stress responses. Although activation of Nrf2 signaling is known to exert anti-inflammatory effects, the function of Nrf2 in inflammation-mediated autoimmune disorders, such as type 1 diabetes, is not well established. To address the roles of Nrf2 in protection against autoreactive T-cell-induced type 1 diabetes, we used non-obese diabetic (NOD) mice, which are a polygenic model of human type 1 diabetes, to generate a genetic model for assessment of the contribution of Nrf2 activation to prevention and/or treatment of type 1 diabetes. Because Keap1 (Kelch-like ECH-associated protein 1) negatively regulates Nrf2, we used Keap1 gene knockdown driven by either hypomorphic or knockout Keap1 alleles, which enhanced Nrf2 signaling to moderate or excess levels, respectively. Nrf2 activation in the NOD:: Keap1 FA/ – mice inhibited T-cell infiltration within or near the islets, ameliorated impairment of insulin secretion and prevented the development of diabetes mellitus. Notably, Nrf2 activation decreased both the plasma interferon-γ (IFN-γ) levels and the IFN-γ-positive cell numbers in the pancreatic islets. The amelioration of diabetes was also observed in the NOD mice with two hypomorphic Keap1 alleles ( Keap1 FA/FA ) by intermediate activation of Nrf2. Both NOD:: Keap1 FA/ – and NOD:: Keap1 FA/FA mice had a decreased incidence of diabetes mellitus, demonstrating that activation of Nrf2 signaling prevented the onset of type 1 diabetes mellitus in NOD mice. Thus, Nrf2 appears to be a potential target for the prevention and treatment of type 1 diabetes.